Effect of Low Diastolic Blood Pressure to Cardiovascular Risk in Patients With Ischemic Stroke or Transient Ischemic Attacks Under Different Systolic Blood Pressure Levels - Chen, Zimo; Mo, Jinglin; Xu, Jie; Dai, Liye; Cheng, Aichun; Yalkun, Gulbahram; Wang, Anxin; Meng, Xia; Li, Hao; Wang, Yongjun (Frontiers in Neurology, 2020)
Background: In the context of recently updated strategies of pressure management, there is a paucity of evidence on the effect of diastolic blood pressure (DBP) level on adverse events among stroke patients. This study aimed to examine the effect of low DBP (<60 mmHg) under different levels of systolic blood pressure (SBP) on the risk of cardiac events and stroke recurrence among patients with ischemic stroke (IS) or transient ischemic attack (TIA). Material and Methods: This study was conducted in 2325 patients with IS or TIA. DBP values were categorized into <60, 60–70, 70–80 (reference), 80–90, and ≥90 mmHg in the main sample and were further categorized as <60 mmHg and ≥60 mmHg (reference) when patients were stratified according to SBP levels (<140, <130, and <120 mmHg). The outcomes were defined as recurrent stroke and cumulative cardiac events (defined as the combination of nonfatal myocardial infarction, nonfatal congestive heart failure, and death) at 1 year. Results: During 1 year of follow-up, a total of 95 cardiac events and 138 stroke recurrences were identified. The patients with low DBP showed a significantly higher risk of cardiac events (hazard ratio [HR]=4.86, 95% confidence interval [CI]=2.54–8.52), especially the elderly patients (≥60 years); however, this result was not observed for stroke recurrence (HR=0.90, 95% CI=0.46–1.74). With the reduction of the SBP levels, the proportion of patients with low DBP increased (6.87%, 12.67%, 34.46%, respectively) and the risk for cardiac events persisted. Conclusions: Along with the new target levels of SBP suggested by updated criteria, there is a trend for DBP to be reduced to a harmfully low level, which was associated with an increased risk of cardiac events among patients with IS or TIA.